Announcements (The Review of Asset Pricing Studies, 2015)
Journal Article Announcements Get access The Review of Asset Pricing Studies, Volume 5, Issue 2, December 2015, Page 155, https://doi.org/10.1093/rapstu/rav009 Published: 03 November 2015